Proteomics of human glomerulonephritis by laser microdissection and liquid chromatography‐tandem mass spectrometry. Issue 4 (9th December 2019) - Kawata, Naoto; Kang, Dedong; Aiuchi, Toshihiro; Obama, Takashi; Yoshitake, Osamu; Shibata, Takanori; Takimoto, Masafumi; Itabe, Hiroyuki; Honda, Kazuho
Abstract: Aim: Laser microdissection (LMD) and liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) enable clinicians to analyse proteins from tissue sections. In nephrology, these methods are used to diagnose diseases of abnormal protein deposition, such as amyloidosis, but they are seldom applied to the diagnosis and pathophysiological understanding of human glomerular diseases. Methods: Renal biopsy specimens were obtained from five patients with IgA nephropathy (IgAN), five patients with membranous nephropathy (MN) and five kidney transplant donors (as controls). From 10‐μm‐thick sections of formalin‐fixed, paraffin‐embedded specimens, 0.3‐mm 2 samples of glomerular tissue were subjected to LMD. The samples were analysed by LC‐MS/MS and investigated clinically and histologically. Results: From the control glomeruli, we identified more than 300 types of proteins. In patients with IgAN, we detected significant increases not only in IgA1 and in C3, but also in the factors related to oxidative stress and cell proliferation in comparison to the controls. In patients with MN, levels of IgG1, IgG4, C3, C4a and phospholipase‐A2‐receptor were significantly elevated in comparison to the controls, as were the aforementioned factors related to oxidative stress and cell proliferations detected in IgAN. Conclusion: Application of LMD and LC‐MS/MS to renal biopsy specimens enabled us to identify not only pathognomonic proteins for the diagnosis, but also several factors possibly involved in the pathogenesis of human glomerular diseases. SUMMARY AT A GLANCE: This paper examined the possible application of laser microdissection and liquid chromatography‐tandem mass spectrometry to renal biopsy specimens to clarify the pathogenesis of human glomerular diseases.